A IMPLEMENTASI COOPERATIVE LEARNING TIPE THINK PAIR SHARE DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA PADA PEMBELAJARAN AL-QUR’AN HADIST: COOPERATIVE LEARNING TIPE THINK PAIR SHARE - mahendra, rifyal tirta (Maliki Interdisciplinary Journal, 2025)
This study aims to improve students' active participation in Al-Qur’an Hadith learning in class XI-C MAN Sumenep through the implementation of the Cooperative Learning method, specifically the Think Pair Share (TPS) type. Active participation is a crucial factor in effective learning, particularly in Islamic Education subjects. This research uses a Classroom Action Research (CAR) approach, conducted in two cycles. Each cycle includes planning, implementation, observation, and reflection stages. The subjects of this study are 36 male students from class XI-C, selected using total sampling. Data collection techniques involved observation, interviews, documentation, and active participation assessment sheets. The data were analyzed both descriptively quantitatively and qualitatively. The results show that the implementation of the TPS model can increase students' active participation. In the pre-cycle phase, students' active participation was at a low level with an average score of 44.4%. After the first cycle, the score increased to 63.9%, and in the second cycle, it further rose to 83.3%. This increase indicates that the TPS model effectively encourages students to be more active in discussions and cooperation during lessons. The study concludes that the TPS learning model can improve students' active participation and create a more interactive learning environment. The implication of this research is the importance of using teaching models that can optimize students' involvement in the learning process.